Mars, A Cosmic Stepping Stone - Nolan, Kevin (Springer, 2017)
The questions of our origin and cosmic abundance of life are among the most compelling facing humanity. We have determined much about the nature and origin of the Universe and our place in it, but with virtually all evidence of our origin long since gone from our world and an unimaginably vast Universe still to explore, defining answers are difficult to obtain. For all of the difficulties facing us however, the planet Mars may act as a ‘cosmic stepping stone’ in uncovering some of the answers. Although different today, the origin and early history of both Earth and Mars may have been similar enough to consider an origin to life on both. But because Mars’ planetary processes collapsed over three billion years ago – just as life was beginning to flourish on Earth – a significant and unique record of activity from that era perhaps relevant to the origin of life still resides there today (....)